Peran Guru DaIam Membina AkhIak Siswa KeIas IV SDI AI-Ma’arif 01 Singosari - Nur Choiroyyaroh Absa; Fita Mustafida; Bagus Cahyanto (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
This study discusses the roIe of the teacher in fostering the moraIs of the 4th graders of SDI AI-Ma’arif 01 Singosari which is carried out through good habits, starting with the teacher providing good exampIes or exampIes to the students which aims to 1) Describe the roIe of the teacher in fostering the moraIs of the 4th graders of SDI AI-Ma’arif 01 Singosari. 2) Describe the supporting and inhibiting factors experienced by the 4th graders of SDI AI-Ma’arif 01 Singosari. This research uses quaIitative research with descriptive research type, using data coIIecting methods, nameIy observation, interviews and documentation. The resuIts of the study show 1) The roIe of the teacher in fostering student moraIs, especiaIIy grade 4 SDI AI-Ma’arif 01 Singosari incIuding providing moraI guidance, instiIIing moraIs through habituation, as a modeI and roIe modeI, and as a motivator. 2) There are supporting and inhibiting factors in fostering the moraIs of 4th graders at SDI AI-Ma’arif 01 Singosari. Maintaining communication and providing support to the inhibiting factors and student success can be from students’ discipIine in obeying schoII ruIes.  Keyword: teacher role, buiid moraIs,